Determination of Optimum Condition for the Production of Rice Husk‐Derived Bio‐oil by Slow Pyrolysis Process - Yiin, Chung Loong; Suzana, Yusup; Chiang, Jinn Tan; Bawadi, Abdullah (John Wiley & Sons, Ltd., 2015)
Recently, studies on bio‐oil have captured international interest in developing it as an alternative energy option. Bio‐oil which is also known as pyrolysis oil or bio‐fuel oil was produced by pyrolysis process without any additional oxygen. Biomass pyrolysis essentially converts 80–95% of the feed material to gases and bio‐oil. This chapter provides an overview of how to produce bio‐oil through slow pyrolysis of rice husk (RH) at different heating rates in order to determine the optimum reaction condition that will give maximum liquid yield. The characteristics of bio‐oil produced at different heating rates are then analyzed. The chemical compound of bio‐oil product was analyzed by using gas chromatography‐mass spectroscopy (GC‐MS). The bio‐oil produced at different heating rates is analyzed for its chemical composition. The higher number of phenol and acid compounds contributes to the higher pH number of bio‐oil that was produced at a heating rate of 20°C/min.